2022
DOI: 10.1093/sleep/zsac079.468
|View full text |Cite
|
Sign up to set email alerts
|

0471 Identifying Trauma-Informed Adaptations to Cognitive Behavioral Therapy for Insomnia among Women Veterans: Results of an Expert Panel

Abstract: Introduction Trauma-informed care is an emerging area of health services research. While trauma-focused care specifically targets symptoms of posttraumatic stress disorder (PTSD), trauma-informed care involves tailoring interventions to meet the unique needs of patients who have experienced trauma. Insomnia and PTSD are common comorbid disorders, but no known previous studies have identified trauma-informed adaptations to cognitive behavioral therapy for insomnia (CBT-I). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…TIC is a framework for acquiring trauma knowledge and responses and supporting appropriate responses for traumatized individuals. TIC is offered in the community as well as in medical institutions ( Mahon, 2022 ) and can be applied in occupational health settings ( Rosemberg et al, 2017 ), as cognitive behavioral therapy that includes TIC has been reported to improve insomnia in PTSD ( Carlson et al, 2022 ), TIC could be practiced in occupational health settings to improve insomnia in workers with ACEs.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…TIC is a framework for acquiring trauma knowledge and responses and supporting appropriate responses for traumatized individuals. TIC is offered in the community as well as in medical institutions ( Mahon, 2022 ) and can be applied in occupational health settings ( Rosemberg et al, 2017 ), as cognitive behavioral therapy that includes TIC has been reported to improve insomnia in PTSD ( Carlson et al, 2022 ), TIC could be practiced in occupational health settings to improve insomnia in workers with ACEs.…”
Section: Discussion/conclusionmentioning
confidence: 99%